Neurotrophic Keratopathy Post-Herpes Zoster Ophthalmicus Infection - Sarasati, Fani; Zuhria, Ismi (Universitas Airlangga, 2025)
Introduction: Neurotrophic keratopathy (NK) is a degenerative disease of the corneal epithelium caused by disruption of corneal trigeminal innervation, resulting in reduced corneal sensitivity, epithelial damage, and impaired corneal healing. It can be caused by various factors, such as viral infections (e.g. herpes simplex keratoconjunctivitis and herpes zoster), chemical or physical trauma, corneal surgery, and intracranial lesions. Management of NK is based on clinical severity to promote corneal healing and prevent progression to stromal melting or perforation. Case Presentation: A 64-year-old male presented with a three-month history of a whitish plaque on the right eye, accompanied by redness, foreign body sensation, and decreased vision. The patient had a history of herpes zoster ophthalmicus (HZO) on the left side of the forehead in June 2022. Ophthalmologic examination revealed a 4 x 5 mm corneal epithelial defect with stromal infiltrates and decreased corneal sensitivity in the left eye, consistent with stage 2 neurotrophic keratopathy. Ancillary tests revealed reduced tear production and instability of the tear film. The patient was treated with topical antibiotics, lubricants, cycloplegics, and systemic doxycycline, with weekly follow-up and no evidence of active bacterial or fungal infection. Conclusion: Neurotrophic keratopathy can occur as a complication of post-HZO infection. Early diagnosis, severity-based treatment, and close monitoring are crucial for achieving epithelial healing and preventing further corneal damage. Prognosis depends on the degree of sensory impairment and the response to treatment.